Violence & society - Ray, Larry J. (Thousand Oaks, Calif. : SAGE, 2011)
In this compelling work, Larry Ray offers a wide-ranging and integrated account of the many manifestations of violence in society. He examines violent behaviour and its meanings in contemporary culture and throughout history.
Includes bibliographical references (p. [198]-218) and index.
Keywords: Violence -- Social aspects; Violence; Violence -- Psychological aspects